Dal'nii Vostok . Dal'nii Vostok . The Far East . Дальний Восток - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Energy crisis at the Far East; rise of the prices for locally grown vegetables and fruits in comparison with the imported tropical fruits; the visit of the Russian Minister of Foreign Affairs, Andrei Kozyrev, to Blagoveshchensk; the new customs point on the Russian-Japanese border; the problem of adopting Russian children by foreigners; Vladimir Vysotsky's birthday; building of the cosmodrome at the Far East; the opening of the theater studio "Chamber opera" in Vladivostok. Contributors: Voropaev, Vladimir (Anchor) Энергетический кризис на Дальнем Востоке; рост цен местных фруктов и овощей в сравнении с импортными тропическими фруктами; визит министра иностранных дел России, Андрея Козырева, в Благовещенск; новый таможенном пункте на границе Китая и России; открытие двух новых авиа-маршрутов между Россией и Японией; проблема усыновления русских детей иностранцами; день рождения Владимира Высоцкого; строительство Космодрома на Дальнем Востоке; открытие театра-студии "Камерная Опера" во Владивостоке. Создатели: Воропаев, Владимир (Ведущий/Ведущая)